Cationic R‐Substituted‐Indenyl Nickel(II) Complexes of Arsine and Stibine Ligands: Synthesis, Characterization, and Catalytic Behavior in the Oligomerization of Styrene. Issue 5 (25th January 2018) - Gomes, Clara S. B.; Costa, Sandra I.; Silva, Leonel C.; Jiménez‐Tenorio, Manuel; Valerga, Pedro; Puerta, M. Carmen; Gomes, Pedro T.
Abstract : A series of new cationic R n ‐substituted‐indenyl nickel(II) complexes containing arsine or stibine ligands were synthesized in moderate to very high yields by the protonation of the corresponding bis(indenyl) nickel derivatives [Ni(η‐R n ‐Ind)2 ] with HBF4, in the presence of 2 equiv. of AsPh3 or SbPh3 donor ligands. These complexes, with the general formula [Ni(η‐R n ‐Ind)(EPh3 )2 ]BF4 (E = As, Sb), were structurally characterized by NMR spectroscopy and X‐ray diffraction, and subsequently tested as single‐component catalysts for the oligomerization of styrene, leading to the formation of very low molecular weight head‐to‐tail oligomers (typically consisting of dimers, trimers and tetramers). The new 1‐ or 2‐monosubstituted‐indenyl Ni II catalyst precursors exhibit extremely high catalytic activities, considerably higher than those observed for the symmetrical unsubstituted‐ and the 1, 3‐disubstituted‐indenyl nickel analogues (i.e. monosubstituted >> non‐substituted > 1, 3‐disubstituted), their reactivity pattern showing similarities with that of the corresponding allyl derivatives. A simpler and more straightforward experimental procedure for the high yield preparation of [NiBr2 (DME)], an important nickel starting material, which was used in the preparation of the bis(indenyl) nickel precursors of this work, is also described. Abstract : New cationic R‐substituted‐indenyl nickel(II) complexes of stibine and arsine ligands are highly active catalysts for the oligomerization of styrene.